2021
DOI: 10.1111/ced.14896
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and cutaneous reactions following inactivated SARS‐CoV‐2 vaccine (CoronaVac ® ) in healthcare workers

Abstract: and one-third (33.9%) were 'not confident' or 'not at all confident' in managing skin conditions in patients with SOC (Fig. 1c). Lack of exposure to patients with SOC was cited by 60.7% of participants as the biggest challenge to looking after these patients (Fig. 1d), which was not an unexpected finding, as 67.9% of respondents estimated that < 5% of their patients had SOC. Specific conditions that were noted to be difficult to diagnose or manage included (i) inflammatory dermatoses (n = 29) such as atopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
2
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 3 publications
(9 reference statements)
0
21
2
2
Order By: Relevance
“…Considering the additive components in CoronaVac, it does not contain the ones (except sodium chloride) similar in the drugs which the patients had a HSR history with. However, there are some reports demonstrating HSRs to CoronaVac [ 33 , 34 , 35 ]. Urticaria was detected as the most common cutaneous reaction in healthcare workers vaccinated with CoronaVac [ 33 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the additive components in CoronaVac, it does not contain the ones (except sodium chloride) similar in the drugs which the patients had a HSR history with. However, there are some reports demonstrating HSRs to CoronaVac [ 33 , 34 , 35 ]. Urticaria was detected as the most common cutaneous reaction in healthcare workers vaccinated with CoronaVac [ 33 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, there are some reports demonstrating HSRs to CoronaVac [ 33 , 34 , 35 ]. Urticaria was detected as the most common cutaneous reaction in healthcare workers vaccinated with CoronaVac [ 33 ]. Most of the HSRs in a latter study were mild except 1 case of anaphylaxis.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In a study by Durmaz et al, who used an e‐mail survey to evaluate 221 healthcare professionals vaccinated with CoronaVac, 33 cutaneous reactions were reported, with the most common being urticaria. 6 In two case series, one including seven patients 8 and the other including six patients, 7 urticaria/angioedema was the most observed cutaneous reactions. In the current study, after the CoronaVac vaccine, type 1 immediate type reactions were observed, such as urticaria/angioedema and anaphylaxis and type 4 delayed‐type reactions, including petechial rash, dyshidrotic eczema, lichenoid reaction, erythema multiforme, contact dermatitis, delayed large local reaction, symmetrical drug‐related intertriginous and flexural exanthema, and maculopapular rash.…”
Section: Discussionmentioning
confidence: 96%
“… 1 , 2 Population‐based, 3 hospital‐based, 4 and international registry‐based 5 studies have also been undertaken to investigate the cutaneous adverse reactions to the BioNTech vaccine. However, there are only small‐scale studies 6 and case series 7 , 8 concerning the cutaneous adverse reactions to the CoronaVac vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Most of reactions improved within few weeks of onset without treatment. 1 However, there are no reports of the inactivated vaccine as a trigger of pityriasis rubra pilaris (PRP).…”
mentioning
confidence: 99%